2019
DOI: 10.1051/0004-6361/201935133
|View full text |Cite
|
Sign up to set email alerts
|

Modelling ion populations in astrophysical plasmas: carbon in the solar transition region

Abstract: The aim of this work is to improve the modelling of ion populations in higher density, lower temperature astrophysical plasmas, of the type commonly found in lower solar and stellar atmospheres. Ion population models for these regions frequently employ the coronal approximation, which assumes conditions more suitable to the upper solar atmosphere, where high temperatures and lower densities prevail. These assumptions include all ion charge-states being in the ground state, and steady-state equilibrium where th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Concerning free electron processes in the lower atmosphere, Dufresne & Del Zanna (2019) and Dufresne et al (2020) show for carbon and oxygen that suppression of dielectronic recombination (DR) and ionisation and recombination from metastable levels notably alter ion formation. The latter effect is relatively stronger than the former in altering the charge state distribution for the first few charge states.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning free electron processes in the lower atmosphere, Dufresne & Del Zanna (2019) and Dufresne et al (2020) show for carbon and oxygen that suppression of dielectronic recombination (DR) and ionisation and recombination from metastable levels notably alter ion formation. The latter effect is relatively stronger than the former in altering the charge state distribution for the first few charge states.…”
Section: Methods and Datamentioning
confidence: 99%
“…The present work is part of a series of papers with the aim of building on those pioneering works, in order to answer the questions raised above, and to provide modelling suitable for the transition region. Dufresne & Del Zanna (2019) and Dufresne et al (2020) develop the coronal approximation of carbon and oxygen by adding the effects modelled by Burgess & Summers (1969) and Nussbaumer & Storey (1975). It is shown that, by including the effects of density on the electron collisional processes, predicted intensities are in better agreement with observations for the lines emitted below 100 000 K, when compared to coronal approximation modelling.…”
Section: Introductionmentioning
confidence: 99%
“…As it turns out that CI from (populated) excited states is very important for the calculation of the charge state distribution, an effort is ongoing to calculate DI with FAC, and EA with the available R-matrix CE rates. Rates for the carbon and oxygen ions have been produced [55,56], and further work is ongoing.…”
Section: Collisional Ionization (Ci) Ratesmentioning
confidence: 99%
“…One way to estimate the DR suppression is therefore to use the recent DR project rates and apply the variation with density found by [67]. This approximation has been adopted by [55,56] using directly the effective rates of [67], and by [68] using the empirical formulae of [69] which aim to reproduce the same effective rates. The [69] formulae will be introduced in CHIANTI version 10 to improve the modeling of high density plasma (on a side note, earlier empirical formulae by [70] were affected by a few problems).…”
Section: Recombination Ratesmentioning
confidence: 99%
See 1 more Smart Citation